Solid-phase reverse transfection for intracellular delivery of functionally active proteins - Bulkescher, Ruben; Starkuviene-Erfle, Vytaute; Erfle, Holger (Genome research, 2017)
An international, peer-reviewed genome sciences journal featuring outstanding original research that offers novel insights into the biology of all organisms
Published in advance September 5, 2017
Gesehen am 21.06.2018